Zentrum in der Peripherie. Nationalitätenpolitik in der SSR Georgien - Oliver Musa Noyan (Historia.scribere)
The following bachelor thesis will deal with the policy of national minorities in the Soviet Republic of Georgia and its impact on the wars of secession in the early 1990s. The analysis will be framed in a center- periphery model to explain the complex struggle between the soviet authorities in Moscow and Tbilisi on the one hand, and Tbilisi and its autonomous regions of Abkhazia and South Ossetia on the other hand throughout the 20th century. The paper tries to examine the contemporary ethnic conflicts in Georgia though the lenses of an historical conflict-analysis to show the deeper historical roots of those frozen conflicts and the effects of the policy of nationalities in the Soviet Union on those conflicts.